Penerapan Metode Entropy dan WASPAS dalam Rekomendasi Pemilihan Laptop Desain Grafis Terbaik - Gogor Christmass Setyawan; Legito Legito; Indah Kusuna Dewi; Dahlan Abdullah; Jeperson Hutahaean (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Laptops are currently one of the basic needs that are growing to become electronic devices that are widely used by the public. Laptops have various features and specifications that support graphic design activities. Supportive laptops can influence studying the field of graphic design because laptops that have specifications that are appropriate to activities will facilitate and support activities, whereas if you use a laptop that does not have the appropriate specifications, it will hinder activities and not even be able to carry out these activities. Users who want to learn about graphic design are confused about choosing the best graphic design laptop from the many choices of laptops currently available. In determining the decision to choose the best suitable graphic design laptop, it must be able to meet the criteria, including Processor, RAM, Hard Drive, VGA Type, VGA Capacity, Weight and Price. Because of this problem, a system is needed that can solve existing problems, namely a decision support system by combining the ENTROPY and WASPAS (Weighted Aggregated Sum Product Assessment) methods which aim to obtain the value and preference weight of the first ranking alternative. So that the recommendation for a graphic design laptop is the RAZER BLADE 15 ADVANCED which is in the A4 alternative with the first recommendation with the highest score of 3.79720